Heavy metal ATPase 3 (HMA3) confers cadmium hypertolerance on the cadmium/zinc hyperaccumulator Sedum plumbizincicola - Liu, Huan; Zhao, Haixia; Wu, Longhua; Liu, Anna; Zhao, Fang‐Jie; Xu, Wenzhong (The New phytologist, 2017)
Cadmium (Cd) is highly toxic to most organisms, but some rare plant species can hyperaccumulate Cd in aboveground tissues without suffering from toxicity. The mechanism underlying Cd detoxification by hyperaccumulators is interesting but unclear. Here, the heavy metal ATPase 3 (SpHMA3) gene responsible for Cd detoxification was isolated from the Cd/zinc (Zn) hyperaccumulator Sedum plumbizincicola. RNA interference (RNAi)-mediated silencing and overexpression of SpHMA3 were induced to investigate its physiological functions in S. plumbizincicola and a nonhyperaccumulating ecotype of Sedum alfredii. Heterologous expression of SpHMA3 in Saccharomyces cerevisiae showed Cd-specific transport activity. SpHMA3 was highly expressed in the shoots and the protein was localized to the tonoplast. The SpHMA3-RNAi lines were hypersensitive to Cd but not to Zn, with the growth of shoots and young leaves being severely inhibited by Cd. Overexpressing SpHMA3 in the nonhyperaccumulating ecotype of S. alfredii greatly increased its tolerance to and accumulation of Cd, but not Zn. These results indicate that elevated expression of the tonoplast-localized SpHMA3 in the shoots plays an essential role in Cd detoxification, which contributes to the maintenance of the normal growth of young leaves of S. plumbizincicola in Cd-contaminated soils.